Strategic visions for labour administration in the Caribbean : a compilation of reports - Mulvey, Kieran (ILO Port of SpainTT, 2003)
Presents a comprehensive assessment of the operations of labour administrations in the Caribbean. Offers recommendations on how they can effectively transform themselves to become principal actors in the development of the region.